Aging effect on step adjustments and stability control in visually perturbed gait initiation - Sun, Ruopeng; Cui, Chuyi; Shea, John B. (Gait & posture, 2017)
•Novel method was used to assess step adjustments during gait initiation.•Step adjustment direction and timing affect stepping accuracy and gait stability.•Older adults exhibited greater undershoot in foot placement.•Older adults were unable to restore dynamic stability in a fast manner. Gait adaptability is essential for fall avoidance during locomotion. It requires the ability to rapidly inhibit original motor planning, select and execute alternative motor commands, while also maintaining the stability of locomotion. This study investigated the aging effect on gait adaptability and dynamic stability control during a visually perturbed gait initiation task. A novel approach was used such that the anticipatory postural adjustment (APA) during gait initiation were used to trigger the unpredictable relocation of a foot-size stepping target. Participants (10 young adults and 10 older adults) completed visually perturbed gait initiation in three adjustment timing conditions (early, intermediate, late; all extracted from the stereotypical APA pattern) and two adjustment direction conditions (medial, lateral). Stepping accuracy, foot rotation at landing, and Margin of Dynamic Stability (MDS) were analyzed and compared across test conditions and groups using a linear mixed model. Stepping accuracy decreased as a function of adjustment timing as well as stepping direction, with older subjects exhibited a significantly greater undershoot in foot placement to late lateral stepping. Late adjustment also elicited a reaching-like movement (i.e. foot rotation prior to landing in order to step on the target), regardless of stepping direction. MDS measures in the medial-lateral and anterior-posterior direction revealed both young and older adults exhibited reduced stability in the adjustment step and subsequent steps. However, young adults returned to stable gait faster than older adults. These findings could be useful for future study of screening deficits in gait adaptability and preventing falls.